Empowering women in Abbasid poetry (women of the palace as an example) - Dr. Wisam Mohammed Aboud Thamer Al-Rubaie; Dr. Marwa Ali Hussein Al-Qurashi (Journal of College of Education, 2024)
When we looked at Abbasid poetry, we found many examples that showed great development in protecting the Abbasid woman, empowering her, and glorifying her status, As a result, the research explained to us the high status of the Abbasids politically and socially and how this was represented in poetry, which revealed to us the secrets of the souls of kings and poets and expressed the great influence that women possessed in the court of the Abbasid caliphs, This development was not limited to the political aspect, but rather extended to the social aspect, which The status of women changed positively, She enjoyed unprecedented freedom, joined the kingdom of writers, competed with poets and excelled at them in what they used to excel at, and the development in empowerment led to enhancing women’s self-confidence. Which resulted in cultural and scientific development that gave women their rights and granted them most of their desires and wishes.
Keywords: development, protection, empowerment, women, woman, Abbasid, caliphs, society, politics, literature, poetry.